Rights at work in times of crisis: trends at the country-level in terms of compliance with international labour standards - Tajgman, David; Saget, Catherine; Elkin, Natan; Gravel, Eric (Geneva, 2011)
"This paper seeks to identify trends in rights at work during the global financial and economic crisis that began in 2008, in terms of international labour standards. Its primary sources of information use recent observations of the International Labour Organisation’s Committee of Experts on the Application of Conventions and Recommendations (CEACR) relating to the crisis, as well as data collected in the ILO/World Bank inventory standardized questionnaire of policy responses to the crisis on a sample of 50 countries covering the period mid-2008 - mid-2010."